Q: The question just says, evaluate the polynomial. -2x^2-y^2+xy, when x=-3 and y=5.

A: This conversation has been flagged as incorrect. New answers have been added below ....

Expert answered|Rosafe|Points 30|

Question

Asked 8/5/2012 8:51:18 PM

Updated 7/4/2014 5:33:33 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/4/2014 5:33:33 PM]

Rating

3

-2x^2 - y^2 + xy, when x =- 3 and y = 5

-2(-3)^2 - 5^2 + (-3)(5)

= -2(9) - 25 - 15

= -18 - 25 - 15

= -43 - 15

= -58

-2(-3)^2 - 5^2 + (-3)(5)

= -2(9) - 25 - 15

= -18 - 25 - 15

= -43 - 15

= -58

Added 7/4/2014 5:33:32 PM

This answer has been confirmed as correct and helpful.

Simplify. -12y-8x-4x **Weegy:** -12y + -8x + -4x = -12x - 12y
(More)

Question

Expert Answered

Updated 6/25/2014 3:35:51 PM

0 Answers/Comments

Evaluate the polynomial. -2^2-y^2+xy, when x=-3 and y=5 **Weegy:** Can you make the question more clear? We'd like to answer this question. Thanks. (More)

Question

Expert Answered

Updated 7/8/2014 4:44:57 AM

1 Answer/Comment

-2^2-y^2+xy, when x=-3 and y=5

-2^2 - 5^2 + (-3)(5)

= -4 - 25 - 15

= -29 - 15

= -44

-2^2 - 5^2 + (-3)(5)

= -4 - 25 - 15

= -29 - 15

= -44

Added 7/8/2014 4:44:55 AM

This answer has been confirmed as correct and helpful.

Factor: x^2-25 Factor: 9x^2-4y^2 **Weegy:** Is there an = in this equation anywhere? (More)

Question

Expert Answered

Updated 7/8/2014 4:46:55 AM

1 Answer/Comment

x^2 - 25 = (x - 5)(x + 5)

9x^2 - 4y^2 = (3x - 2y)(3x + 2y)

9x^2 - 4y^2 = (3x - 2y)(3x + 2y)

Added 7/8/2014 4:46:54 AM

This answer has been confirmed as correct and helpful.

26,995,736 questions answered

There are no comments.